Microbial mineralization induced flood prevention preparation stone and preparation method thereof
Through microbial mineralization induction technology, combined with Yellow River sediment and other materials, the problem of insufficient strength of existing Yellow River sediment materials has been solved, and high-strength and low-cost preparation of flood prevention stones has been achieved, and good durability and environmental protection have been achieved. performance.
Patent Information
- Application Number
- CN202411721745.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing Yellow River sediment materials have low strength and are difficult to meet the strength standards for building materials. The alkali-induced gelling materials have complex processes and high costs.
Using microbial mineralization induction technology, the composite gel material is formed through the combination of microbial mineralization repair agent, alumina, slag powder, sediment, microbial cementitious liquid and steel fibers, and the mineralization reaction is activated through urea hydrolysis reaction to improve the Yellow River. Mineralization efficiency and mechanical properties of silt.
It significantly improves the strength and stability of flood prevention stones, enhances the anti-seepage performance and corrosion resistance, reduces production costs, and reduces environmental pollution.
Smart Images

Figure BDA0005158212980000051
Abstract
Description
Technical Field
[0001] The invention relates to flood prevention stones, and in particular to a microbial mineralization induced flood prevention stone and a preparation method thereof. Background Art
[0002] The Yellow River silt has certain volcanic ash activity. The Yellow River silt, which is mainly composed of silicon and aluminum components such as SiO2, Al2O3, and Fe2O3, is used as the basic raw material. It contains fewer mineral components that can be converted into cementitious products. The strength of the Yellow River silt materials developed with the help of alkali-activated modification technology is generally low and it is difficult to meet the strength standards for building materials. The activator is the key to the preparation of alkali-activated cementitious materials. The composition and parameters of the activator are the main reasons affecting the performance of alkali-activated cementitious materials, but the process is complicated and the cost is high. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a microbial mineralization induced flood prevention stone and a preparation method to solve the problems existing in the above-mentioned existing methods.
[0004] Technical solution: In the first aspect, some embodiments of the present disclosure propose a microbial mineralization induced flood control stone, which includes: 3-5 parts of microbial mineralization repair agent, 3-5 parts of alumina, 33-38 parts of slag powder, 42-45 parts of mud and sand, 9-12 parts of microbial cementing liquid, and 2-3 parts of steel fiber.
[0005] Optionally, the chemical composition of the silt in the above-mentioned flood prevention and prevention stone contains SiO2, Al2O3, Fe2O3, CaO and MgO, with a total percentage of 89.53%, and the silt serves as the main aggregate.
[0006] Optionally, the microbial cementing liquid in the above-mentioned flood prevention and prevention stone is a mixture of calcium chloride and urea in a molar mass ratio of 1:1, with a concentration of 0.25-1.00 mol / L. Urea is hydrolyzed under the action of the microbial mineralization repair agent to generate carbonate ions, which react with calcium chloride to generate calcium carbonate precipitates, which can cement mud and sand.
[0007] Optionally, the alumina in the above-mentioned flood prevention stone is alumina that passes through a 0.15-0.075mm sieve and has a purity of 98.0%. Alumina can effectively reduce the pH value of the action environment of the microbial mineralization repair agent, provide adsorption sites for microorganisms, promote bacterial adsorption, and thus significantly improve the mineralization efficiency.
[0008] In a second aspect, some embodiments of the present disclosure provide a method for preparing microbial mineralization-induced flood prevention stone.
[0009] The preparation method comprises: inoculating microorganisms with mineralization and deposition functions into a sterilized liquid culture medium for cultivation, adding the microorganisms into a protective agent, mixing and drying the agent to obtain a microbial mineralization repair agent;
[0010] Calcium chloride and urea are mixed and stirred to obtain a microbial cementing liquid;
[0011] The microbial mineralization repair agent and alumina are mixed and then slag powder is added and stirred to obtain a composite gel material, wherein the addition of alumina is used to reduce the pH value and promote bacterial adsorption, and the slag powder is added to stabilize the microbial mineralization repair agent and alumina to form a gelling material;
[0012] After the composite gel material and sediment are mixed in a preset ratio, a microbial cementing liquid is added to obtain a mixed slurry. The mixed slurry undergoes a urea hydrolysis reaction, activating the mineralization reaction and starting to mineralize the Yellow River sediment.
[0013] Slowly add steel fiber into the mixed slurry, stir evenly and then press into shape, and then curing and demoulding to obtain the sample. The addition of steel fiber can enhance the mechanical properties of microbial mineralized Yellow River sediment and improve its stability and durability.
[0014] The samples were subjected to standard curing and carbon curing in turn to obtain flood control stones. Standard curing allows the microbial mineralization reaction to be complete, improves the uniformity of microbial mineralization, and ensures that the flood control stones obtain the required strength and stability in the early stages; carbon curing exposes the flood control stones to a carbon dioxide environment to simulate the carbonization that may be encountered during long-term use, and further evaluates the durability and anti-carbonization performance of the flood control stones in long-term use. Carrying out these two curing steps in sequence can comprehensively evaluate the performance of flood control stones and ensure their reliability and safety in practical applications.
[0015] Optionally, the microorganisms having mineralization and deposition functions are inoculated in a sterilized liquid culture medium for culture, and then added to a protective agent, mixed and dried to obtain a microbial mineralization repair agent, including:
[0016] Inoculate the microorganisms with mineralization and deposition function into a sterilized liquid culture medium solution, place the solution in a shaker, and culture the solution at a constant temperature of 10-40°C and 50-200 r / min for 12-60 hours to obtain a bacterial solution containing microorganisms;
[0017] The bacterial liquid containing microorganisms is centrifuged at 10-40°C and 2000-5000 r / min for 10-40 min to obtain bacterial sludge;
[0018] The bacterial sludge was diluted with distilled water to an OD600 value of 0.4-3.0 to obtain a bacterial solution;
[0019] The bacterial mud is added to the protective agent, mixed with an oscillator to prepare a bacterial suspension, and then dried at 25-65° C. to obtain bacterial powder, so that the microorganisms in the bacterial powder exist in the form of spores.
[0020] Optionally, the microorganisms having mineralization and deposition function include at least one of urease-producing bacteria, non-urease-producing bacteria, aerobic mixed bacteria, anaerobic mixed bacteria, and facultative anaerobic mixed bacteria.
[0021] Optionally, the protective agent is at least one of glucose, lactose, mannitol, sorbitol, glycine, glutamic acid, sodium chloride and calcium carbonate.
[0022] Optionally, the calcium chloride and urea are mixed and stirred to obtain a microbial cementing liquid, comprising:
[0023] Deionized water and calcium chloride are mixed to prepare a calcium chloride solution;
[0024] Calcium chloride solution and urea were mixed in a mass molar ratio of 1:1 and then magnetically stirred to obtain a microbial cementing liquid with a concentration of 0.25-1.00 mol / L.
[0025] Optionally, the sample is subjected to standard curing and carbon curing in turn to obtain flood prevention stone, including:
[0026] The method comprises: after the sample is formed, it is placed in an environment with a relative humidity of 60±5% and a temperature of 20±2°C for curing for 24 hours, then demolded, and then standardly cured in this environment until the age of 28 days; then the sample is placed in a carbon curing box with a relative humidity of 60±5%, a carbon dioxide volume fraction of 50-95%, and a pressure of 0.1-0.3MPa for curing for 2-12 hours.
[0027] Beneficial effects:
[0028] The embodiments of the present disclosure use mud and sand as the main raw materials, add microorganisms to accelerate mineralization, accelerate the hydration of carbon dioxide, achieve deconstruction and recombination of active materials, and use aluminum oxide to reduce the pH value of the microbial growth environment and provide microbial adsorption sites, thereby improving mineralization efficiency, synergizing with steel fibers, and improving the corrosion resistance and strength of the stone. DETAILED DESCRIPTION
[0029] The present invention will be further described below with reference to specific examples.
[0030] Example 1
[0031] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight: 5 parts of microbial mineralization repair agent, 5 parts of aluminum oxide, 36 parts of slag powder, 42 parts of Yellow River silt, 10 parts of microbial cementing liquid, and 2 parts of steel fiber.
[0032] Example 2
[0033] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight: 4 parts of microbial mineralization repair agent, 4 parts of aluminum oxide, 34 parts of slag powder, 45 parts of Yellow River silt, 10 parts of microbial cementing liquid, and 2 parts of steel fiber.
[0034] Example 3
[0035] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight: 3 parts of microbial mineralization repair agent, 3 parts of aluminum oxide, 34 parts of slag powder, 45 parts of Yellow River silt, 12 parts of microbial cementing liquid, and 3 parts of steel fiber.
[0036] Example 4
[0037] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight: 4 parts of microbial mineralization repair agent, 4 parts of aluminum oxide, 38 parts of slag powder, 42 parts of Yellow River silt, 10 parts of microbial cementing liquid, and 2 parts of steel fiber.
[0038] Example 5
[0039] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight, 5 parts of microbial mineralization repair agent, 5 parts of aluminum oxide, 35 parts of slag powder, 43 parts of Yellow River silt, 9 parts of microbial cementing liquid, and 3 parts of steel fiber.
[0040] Example 6
[0041] A microbial mineralization-induced flood prevention and stone prevention material, the raw materials of which include, by weight, 9 parts of microbial mineralization repair agent, 1 part of aluminum oxide, 35 parts of slag powder, 43 parts of Yellow River silt, 9 parts of microbial cementing liquid, and 3 parts of steel fiber.
[0042] The preparation methods of the microbial mineralization-induced flood prevention stones of Examples 1-6 are the same, and the specific preparation methods include the following steps:
[0043] Inoculate a microbial strain with mineralization and deposition function into a sterilized liquid culture medium solution, wherein the microbial strain with mineralization and deposition function is any one of urease-producing bacteria, non-urease-producing bacteria, aerobic mixed bacteria, anaerobic mixed bacteria, and facultative anaerobic mixed bacteria; place the liquid culture medium solution inoculated with the microbial strain in a shaker; culture the bacterial solution at a constant temperature of 10-40° C. and 50-200 r / min for 12-60 hours to obtain a bacterial solution containing microorganisms; centrifuge the bacterial solution at 10-40° C. and 2000-5000 r / min for 10-40 minutes to obtain bacterial mud; dilute the bacterial mud with distilled water to an OD600 value of 0.4-3.0 to obtain a bacterial solution; add the bacterial mud into a protective agent and mix to prepare a bacterial suspension; dry at 25-65° C. to obtain bacterial powder, so that the microorganism exists in the form of spores and is stable in storage;
[0044] Mix deionized water and calcium chloride to prepare a calcium chloride solution, weigh urea in a molar mass ratio of 1:1 to calcium chloride and mix with the calcium chloride solution, and stir with a magnetic stirrer to obtain a microbial cementing liquid with a concentration of 0.25-1.00 mol / L;
[0045] Pass Al2O3 through a 0.15-0.075 mm sieve;
[0046] Put the microbial mineralization repair agent, alumina and slag powder into a mixer, dry mix at a stirring speed of 20-30r / min for 1-2min, and stir evenly to obtain a mixed cementitious material;
[0047] Mix the Yellow River silt and the mixed cementitious material, and stir them evenly to obtain a mixed dry material;
[0048] Add the microbial cementing liquid to the obtained mixed dry material, and stir evenly at a stirring speed of 43-53 r / min to obtain a mixed slurry;
[0049] Slowly add steel fiber to the obtained mixed slurry, then stir at a stirring speed of 20-30r / min for 90s and then at a stirring speed of 43-53r / min for 30s, stir evenly, load into a sample making machine in layers, and press into shape at a pressure of 15-20Mpa;
[0050] The samples loaded into the mold are cured, and the mold temperature is tested every 6 hours after the mold is loaded. When it exceeds 40℃, air cooling is performed. After molding, demoulding is performed in an environment of 60±5%RH and 20±2℃ for 24 hours, and then standard curing is performed in this environment until the age of 28 days. Then, curing is performed in a curing box at a relative humidity of 60±5%RH, a volume fraction of 50%-95%CO2, and a pressure of 0.1-0.3MPa for 2-12 hours to obtain flood prevention stone.
[0051] The above embodiments use the Yellow River silt as the main raw material to prepare artificial flood control stones, which have high compactness, high strength, good anti-seepage performance, and can achieve the purpose of resistance to natural erosion. Microbial accelerated mineralization technology is used to accelerate the hydration of carbon dioxide, promote the formation of calcium carbonate, accelerate mineralization, compact structure, and improve product strength. Thereby, the deconstruction and repolymerization of active materials are achieved to form a product structure with better stability and strength. The microorganisms used are microorganisms existing in the natural environment (soil) or the culture of a certain microorganism therein, and the nutrients are also natural substances, which will not cause secondary pollution to the environment. The cost of the nutrient solution used is low. The microbial mineralization method adopted can form minerals with stable properties and strong durability. The carbon dioxide produced in the process can be effectively captured and utilized to mitigate the greenhouse effect. Alumina can effectively reduce the pH value of the bacterial growth environment and can significantly increase the urease activity and calcification efficiency of Bacillus pasteurianus in a high alkaline environment. At the same time, the microvoids of alumina can serve as adsorption sites for bacteria, promoting the adsorption of bacteria, thereby increasing the utilization rate of the bacterial solution. The addition of steel fibers can enhance the shrinkage resistance of artificial stone, enhance the crack resistance, and then enhance the weathering resistance. The synergistic effect of each component makes the stone show excellent corrosion resistance in the natural environment.
[0052] In addition, the use of CO2 curing technology can recycle and fix a large amount of carbon dioxide. Compared with traditional curing methods, this technology not only improves the strength of the stone, but also refines the pore structure of the stone, significantly improving the strength of the stone. This method does not require burning or high-temperature steam curing, saving energy.
[0053] In order to compare the performance of the stone in the above embodiment, a comparative example is set up, using conventional alkali activation preparation technology, and the raw materials include by weight: 5 parts of quicklime, 4 parts of cement, 5 parts of slag powder, 8 parts of fly ash, 65 parts of Yellow River sediment, 1 part of alkali activator, and 10 parts of mixing water. The preparation method of the comparative example adopts a mobile production process. When preparing the defense stone, the mixed slurry with steel fiber is placed in a molding bin, extruded by a special molding equipment, and cut into cubic defense stones by steel wire rope. After natural curing in the bin for 28 days, the finished defense stone can be obtained.
[0054] The prepared defense stones of Examples 1-6 and the comparative example were subjected to physical and mechanical property and durability tests. The test methods were carried out in accordance with the methods specified in "Test Methods for Concrete Blocks and Bricks" (GBT4111-2013). The test results are shown in Table 1.
[0055] From the performance test results in Table 1, it can be seen that with the increase of microbial mineralization repair agent, the strength of the defense stone gradually increases. When the amount of alumina is reduced, the strength of the defense stone will decrease significantly due to the failure to ensure the activity of microorganisms. Compared with the conventional alkali-activated preparation technology in the comparative example, each embodiment has a significant performance improvement.
[0056] Table 1 Performance test data
[0057]
[0058] The above descriptions are only some preferred embodiments of the present disclosure and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present disclosure is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the above-mentioned inventive concept. For example, the above-mentioned features are replaced with the technical features with similar functions disclosed in the embodiments of the present disclosure (but not limited to) and the technical solutions formed.
Claims
1. A microbial mineralization-induced flood prevention and rock prevention method, characterized in that: The raw materials include by weight: 3-5 parts of microbial mineralization repair agent, 3-5 parts of alumina, 33-38 parts of slag powder, 42-45 parts of mud and sand, 9-12 parts of microbial cementing liquid, and 2-3 parts of steel fiber.
2. The microbial mineralization-induced flood prevention and prevention stone according to claim 1, characterized in that: The chemical composition of the silt contains SiO2, Al2O3, Fe2O3, CaO and MgO, with a total percentage of 89.53%.
3. The microbial mineralization-induced flood prevention stone according to claim 1, characterized in that: The microbial cementing liquid is a mixed liquid with a molar mass ratio of calcium chloride to urea of 1:1 and a concentration of 0.25-1.00 mol / L.
4. The microbial mineralization-induced flood prevention and prevention stone according to claim 1, characterized in that: The aluminum oxide is aluminum oxide that passes through a 0.15-0.075 mm sieve and has a purity of 98.0%.
5. A method for preparing microbial mineralization-induced flood prevention stone, characterized in that: The following steps are involved: The microorganisms with mineralization and deposition function are inoculated into a sterilized liquid culture medium for culture, and then added into a protective agent, mixed and dried to obtain a microbial mineralization repair agent; Calcium chloride and urea are mixed and stirred to obtain a microbial cementing liquid; The microbial mineralization repair agent is mixed with alumina, slag powder is added, and the mixture is stirred to obtain a composite gel material; After the composite gel material and the sediment are mixed in a preset ratio, a microbial cementing liquid is added to obtain a mixed slurry; Slowly add steel fiber into the mixed slurry, stir evenly and then press into shape, and then cure and demould to obtain the sample; The samples were cured by standard and carbon curing in turn to obtain flood control preparation stones.
6. The method for preparing the microbial mineralization-induced flood prevention stone according to claim 5, characterized in that: The microorganisms with mineralization and deposition function are inoculated in a sterilized liquid culture medium for culture, and then added to a protective agent, mixed and dried to obtain a microbial mineralization repair agent, including: Inoculate the microorganisms with mineralization and deposition function into a sterilized liquid culture medium solution, place the solution in a shaker, and culture the solution at a constant temperature of 10-40°C and 50-200 r / min for 12-60 hours to obtain a bacterial solution containing microorganisms; Centrifuge the bacterial solution containing microorganisms at 10-40°C and 2000-5000 r / min for 10-40 min to obtain bacterial sludge; The bacterial sludge was diluted with distilled water to an OD600 value of 0.4-3.0 to obtain a bacterial solution; The bacterial sludge is added to the protective agent, mixed with an oscillator to prepare a bacterial suspension, and then dried at 25-65° C. to obtain bacterial powder, so that the microorganisms in the bacterial powder exist in the form of spores.
7. The method for preparing the microbial mineralization-induced flood prevention stone according to claim 5, characterized in that: The microorganisms having the mineralization and deposition function include any one of urease-producing bacteria, non-urease-producing bacteria, aerobic mixed bacteria, anaerobic mixed bacteria, and facultative anaerobic mixed bacteria.
8. The method for preparing the microbial mineralization-induced flood prevention stone according to claim 5, characterized in that: The protective agent is at least one of glucose, lactose, mannitol, sorbitol, glycine, glutamic acid, sodium chloride and calcium carbonate.
9. The method for preparing the microbial mineralization-induced flood prevention stone according to claim 5, characterized in that: The calcium chloride and urea are mixed and stirred to obtain a microbial cementing liquid, comprising: Deionized water and calcium chloride are mixed to prepare a calcium chloride solution; Calcium chloride solution and urea were mixed in a mass molar ratio of 1:1 and then magnetically stirred to obtain a microbial cementing liquid with a concentration of 0.25-1.00 mol / L.
10. The method for preparing the microbial mineralization-induced flood prevention stone according to claim 5, characterized in that: The samples were cured by standard and carbon curing to obtain flood control stones, including: After the sample is formed, it is placed in an environment with a relative humidity of 60±5% and a temperature of 20±2°C for curing for 24 hours and then demolded, and then standardly cured in this environment until the age of 28 days; then the sample is placed in a carbon curing box with a relative humidity of 60±5%, a carbon dioxide volume fraction of 50-95%, and a pressure of 0.1-0.3MPa for curing for 2-12 hours.
Citation Information
Cited By
Solid-waste-based Yellow River sediment cementing material and preparation method of artificial flood prevention preparation stone
CN119954451A